Autocrine IL-10 activation of the STAT3 pathway is required for pathological macrophage differentiation in polycystic kidney disease - Jacqueline D. Peda; Sally M. Salah; Darren P. Wallace; Patrick E. Fields; Connor J. Grantham; Timothy A. Fields; Katherine I. Swenson-Fields (The Company of Biologists, 2016)
Polycystic kidney disease (PKD) is characterized by slow expansion of fluid-filled cysts derived from tubules within the kidney. Cystic expansion results in injury to surrounding parenchyma and leads to inflammation, scarring and ultimately loss of renal function. Macrophages are a key element in this process, promoting cyst epithelial cell proliferation, cyst expansion and disease progression. Previously, we have shown that the microenvironment established by cystic epithelial cells can 'program' macrophages, inducing M2-like macrophage polarization that is characterized by expression of markers that include Arg1 and Il10. Here, we functionally characterize these macrophages, demonstrating that their differentiation enhances their ability to promote cyst cell proliferation. This observation indicates a model of reciprocal pathological interactions between cysts and the innate immune system: cyst epithelial cells promote macrophage polarization to a phenotype that, in turn, is especially efficient in promoting cyst cell proliferation and cyst growth. To better understand the genesis of this macrophage phenotype, we examined the role of IL-10, a regulatory cytokine shown to be important for macrophage-stimulated tissue repair in other settings. Herein, we show that the acquisition of the pathological macrophage phenotype requires IL-10 secretion by the macrophages. Further, we demonstrate a requirement for IL-10-dependent autocrine activation of the STAT3 pathway. These data suggest that the IL-10 pathway in macrophages plays an essential role in the pathological relationship between cysts and the innate immune system in PKD, and thus could be a potential therapeutic target.